THE USE OF CLIMATE INFORMATION FOR DEVELOPING EARLY WARNING SYSTEM TO BROWN PLANT HOPPER ATTACK ON PADDIES - SUSANTI, ERNI; RAMADHANI, F.; JUNE, T.; AMIEN, L.I (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
Crop pests and diseases are limiting factors in determining crops production. Brown Plant Hopper/BPH (Nilaparvata lugens) is the major crop pests and diseases for rice in Asia since 1970?s. The presence of BPH is depending upon several conditions covering pathogenic characteristics, carriers, physical environment (rainfall, temperature, humidity etc.) and biotic environment (natural enemy, competitor organisms). BPH growth is very fast delivering huge amount of eggs, has a short life cycle (28 days) with fast distribution forces and incredible attack forces. BPH is very dynamic in their live assuming due to the climatic condition of their habitat. This is the reason why climate can be used as an indicator for early warning to anticipate the area attack of BPH especially and in general for crop pests and diseases control. The relationship between pest and diseases attack and climate parameters such as rainfall, mean temperature, maximum temperature, minimum temperature, mean humidity, maximum humidity, and minimum humidity can be analyzed using multiple regression. The early warning system is developed using software of MS Access, Arc View, Map Object, and Visual Basic that can be a dynamic and interactive system. The results of analysis showed that climate parameter has a correlation with the area attack of BPH only during the La-Niña years. Those parameters include rainfall, maximumtemperature, maximum temperature at two weeks before attack, minimum temperature, and minimum temperature at two weeks before attack. The early warning system is started by entering the climate prediction for the next cropping season where the time is subject to prediction, at a certain sub-district. After inputting data of climate prediction the system will provide information of potential area attack of BPH at that location. By performing information of potential area attack the anticipative action can be designed earlier so that the crops harvest failure can be reduced.